Love affair [videorecording (DVD)] - McCarey, Leo; McCarey, Leo; Dunne, Irene, 1898-1990; Boyer, Charles, 1899-1978; Ouspenskaya, Maria, 1876-1949 (Criterion collection, 2022)
Two people meet and fall in love aboard a ship crossing the Atlantic Ocean, and upon arriving to New York they separate but agree to meet each other six months later at the top of the Empire State Building.